ESTIMATION OF SNFLUENCE OF GLOBAL FACTORS OF RICK ON THE PROCESS OF FORMING OF INTERNATIONAL TOURIST BRAND - K. Kucherenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
A brand of a territory as an object of tourist interest is the influence of the various risks, which determine the General perception of this territory by tourists. The article is aimed at systematization and estimation of risks that arise in the process of formation of the tourist's country brand. Considered is the problem of influence of global risk factors on the process of formation of international tourist brand. Provides a list of risks, influencing the process of formation of tourist brand. It is noted that these risks can wear both objective and subjective character.